Textbook of rapid response systems concept and implementation - DeVita, Michael A.; Hillman, Ken; Bellomo, R. (Rinaldo) 1956- (Springer, 2011)
Textbook on Rapid Response Systems is designed to assist the medical practitioner or administrator to implement and improve a Rapid Response System, from the logistics of creating a Rapid Response System (including resource allocation, process design, workflow, and training), to the problem of patient safety and quality of care, the evaluation of program results, and engagement in systems research. Written by the world?s leading innovators in the development of Rapid Response Systems, this brand new book takes the place of its groundbreaking predecessor, DeVita, Hillman, and Bellomo, eds., Medical Emergency Teams (Springer, 2006) and includes coverage of pediatric response systems and sepsis response teams, as well as advice, tips, and process guidelines from successful Rapid Response Systems. Textbook of Rapid Response Systems is an invaluable resource for healthcare professionals seeking to improve quality of care in the emergency setting.